Seasonal changes in glacial polynya activity inferred from Weddell Sea varves - D. Sprenk (Climate of the Past, 2014)
The Weddell Sea and the associated Filchner–Rønne Ice Shelf constitute key regions for global bottom-water production today. However, little is known about bottom-water production under different climate and ice-sheet conditions. Therefore, we studied core PS1795, which consists primarily of fine-grained siliciclastic varves that were deposited on contourite ridges in the southeastern Weddell Sea during the Last Glacial Maximum (LGM). We conducted high-resolution X-ray fluorescence (XRF) analysis and grain-size measurements with the RADIUS tool (Seelos and Sirocko, 2005) using thin sections to characterize the two seasonal components of the varves at sub-mm resolution to distinguish the seasonal components of the varves. Bright layers contain coarser grains that can mainly be identified as quartz in the medium-to-coarse silt grain size. They also contain higher amounts of Si, Zr, Ca, and Sr, as well as more ice-rafted debris (IRD). Dark layers, on the other hand, contain finer particles such as mica and clay minerals from the chlorite and illite groups. In addition, Fe, Ti, Rb, and K are elevated. Based on these findings as well as on previous analyses on neighbouring cores, we propose a model of enhanced thermohaline convection in front of a grounded ice sheet that is supported by seasonally variable coastal polynya activity during the LGM. Accordingly, katabatic (i.e. offshore blowing) winds removed sea ice from the ice edge, leading to coastal polynya formation. We suggest that glacial processes were similar to today with stronger katabatic winds and enhanced coastal polynya activity during the winter season. Under these conditions, lighter coarser-grained layers are likely glacial winter deposits, when brine rejection was increased, leading to enhanced bottom-water formation and increased sediment transport. Vice versa, darker finer-grained layers were then deposited during less windier season, mainly during summer, when coastal polynya activity was likely reduced.